Minocycline and Fluconazole Have a Synergistic Effect Against Cryptococcus neoformans Both in vitro and in vivo - Kong, Qinxiang; Cao, Zubai; Lv, Na; Zhang, Hui; Liu, Yanyan; Hu, Lifen; Li, Jiabin (Frontiers in Microbiology, 2020)
In recent decades, the incidence of Cryptococcus neoformans infection, which causes cryptococcosis, has consistently increased. Fluconazole (FLU) is frequently used in the treatment of this disease, mainly in the immunocompromised population, and long-term therapy usually produces drug resistance. Research on antifungal sensitizers has gained attention as a possible means of overcoming this drug resistance. Minocycline (MINO) has an inhibitory effect in vitro on FLU-resistant Candida albicans, and the combination of MINO and FLU has a synergistic effect on FLU-resistant C. albicans. A synergistic effect of MINO/FLU has been reported against C. neoformans, but this effect has not been evaluated on FLU-resistant isolates. This study aimed to investigate the interaction of MINO and FLU against FLU-resistant C. neoformans both in vitro and in vivo. We found that the combination of MINO and FLU had a synergistic effect on FLU-resistant C. neoformans in vitro. For all FLU-resistant strains, the minimum inhibitory concentration (MIC) of FLU decreased significantly when used in combination with MINO, dropping from >128 μg/ml down to 4–8 μg/ml. Additionally, MINO and FLU had a synergistic effect on both susceptible and resistant C. neoformans biofilms, in which the MIC of FLU decreased from >256 μg/ml down to 4–16 μg/ml. Compared with FLU alone, the combination of MINO with FLU prolonged the survival rate of Galleria mellonella larvae infected with FLU-resistant C. neoformans, and also significantly decreased the fungal burden of infected larvae and reduced the tissue damage and destruction caused by FLU-resistant C. neoformans. These findings will contribute to the discovery of antifungal agents and may yield a new approach for the treatment of cryptococcosis caused by FLU-resistant C. neoformans.